2016
DOI: 10.1111/idj.12220
|View full text |Cite
|
Sign up to set email alerts
|

Oral health screening: feasibility and reliability of the oral health assessment tool as used by speech pathologists

Abstract: This is the first study to examine the feasibility and reliability of the OHAT as used by speech pathologists. As the results showed both good feasibility and reliability, the OHAT has the potential to add to the clinical swallowing examination. However, future research investigating actual referral strategies and adaptation of care strategies following assessment with OHAT is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 45 publications
6
38
1
Order By: Relevance
“…Most nondental healthcare professionals involved were nurses, sub-classified as Registered Nurse (RN), Licensed Vocational Nurse (LVN), Clinical Nurse (CN) or Licensed Practical Nurse (LPN). In the study of Simpelaere et al (2016), speech pathologists were included [38]. The population on which the oral health assessment was used was heterogeneous and consisted of rehabilitation residents, nursing home residents, hospitalized older people, community-dwelling older people and older people with mental problems ( Table 2).…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most nondental healthcare professionals involved were nurses, sub-classified as Registered Nurse (RN), Licensed Vocational Nurse (LVN), Clinical Nurse (CN) or Licensed Practical Nurse (LPN). In the study of Simpelaere et al (2016), speech pathologists were included [38]. The population on which the oral health assessment was used was heterogeneous and consisted of rehabilitation residents, nursing home residents, hospitalized older people, community-dwelling older people and older people with mental problems ( Table 2).…”
Section: Included Studiesmentioning
confidence: 99%
“…because of its high ICC and unweighted kappas were reported ( Table 5). Simpelaere et al (2016) investigated the intra-, inter-and test-retest reliability in speech pathologists [38]. However, intra-rater reliability was of "poor" methodological quality as described earlier and will not be further described.…”
Section: Mdsmentioning
confidence: 99%
“…Using the OHAT provided insight into oral health problems. A recent literature review concluded it is the most complete in its items and of best methodological quality in comparison with other oral health assessments (Everaars et al ), but the OHAT is not yet validated in hospitalised patients (Chalmers et al, ; Simpelaere et al, ). Moreover, the OHAT was categorised on a two‐point scale (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The total OHAT score is the sum of the scores for each item. Validation of the OHAT in residential care (Chalmers et al, ; Simpelaere, Van Nuffelen, Vanderwegen, Wouters, & De Bodt, ) showed adequate inter‐rater reliability (interclass correlation coefficient: 0.74–0.96; kappa statistic 0.48–0.80 and 0.83–1.00). In this study, a translated version of the OHAT had been used.…”
Section: Methodsmentioning
confidence: 99%
“…The OHAT consists of eight categories ('lips', 'tongue', 'gums and tissues', 'saliva', 'natural teeth', 'dentures', 'oral cleanliness', and 'dental pain') with three possible scores (0: healthy, 1: some changes present and 2: unhealthy condition) 17) . Scoring of each category is based on structured observation with clear operational definitions.…”
Section: Ohatmentioning
confidence: 99%